2015
DOI: 10.1007/s40865-015-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Incorporate Autonomic Arousal in Developmental and Life-Course Research and Theories

Abstract: Purpose Although there is an extensive body of research on the relationship between autonomic measures of physiological arousal and crime and delinquency, little effort has been made to incorporate autonomic arousal into criminological theories. This article examines the empirical literature on the associations between autonomic arousal and key constructs that are included in developmental and life-course theories, including temperament, cognition, life events, and family factors. Method For an illustrative ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 144 publications
0
14
0
Order By: Relevance
“…More research is clearly needed on biopsychosocial interactions in criminology, and especially on the mechanisms and processes through which they have their effects. The present results show that biological variables should be measured more often in prospective longitudinal studies (Farrington, 2018) and should be included more often in developmental and life-course theories (Choy, Farrington, & Raine, 2015). Furthermore, knowledge about biopsychosocial interactions could be useful in increasing the effectiveness of criminological interventions; it is important to know what is likely to work with whom under what circumstances.…”
Section: Resultsmentioning
confidence: 84%
“…More research is clearly needed on biopsychosocial interactions in criminology, and especially on the mechanisms and processes through which they have their effects. The present results show that biological variables should be measured more often in prospective longitudinal studies (Farrington, 2018) and should be included more often in developmental and life-course theories (Choy, Farrington, & Raine, 2015). Furthermore, knowledge about biopsychosocial interactions could be useful in increasing the effectiveness of criminological interventions; it is important to know what is likely to work with whom under what circumstances.…”
Section: Resultsmentioning
confidence: 84%
“…Both capture autonomic nervous system functioning; skin conductance reflects sympathetic nervous system functioning while heart rate reflects both sympathetic and parasympathetic nervous system activity. Blunted autonomic functioning has been associated with increased antisocial behavior, including violence (Baker et al, 2009; Choy, Farrington, & Raine, 2015; Gao, Raine, Venables, Dawson, & Mednick, 2010; Portnoy & Farrington, 2015). Longitudinal studies have found low resting heart rate in adolescence to be associated with increased risk for criminality in adulthood (Latvala, Kuja-Halkola, Almqvist, Larsson, & Lichtenstein, 2015; Raine, Venables, & Williams, 1990).…”
Section: Psychophysiologymentioning
confidence: 99%
“…Low heart rate indicates low autonomic nervous system activation and provides information on the functioning of both the sympathetic and the parasympathetic nervous systems (Glenn and Raine, 2014). Choy et al (2015) suggested that common developmental and life course criminology perspectives should include biological and psychophysiological markers in explaining criminal behavior and delinquency. The study by Jennings et al (2013) is an example of research that has taken such a perspective, where they investigated the long-term outcomes of RHR measured at age 18.…”
Section: Heart Rate and Criminal Behaviormentioning
confidence: 99%